Exploring Emergent Properties in Chemistry Education: A Philosophical Perspective on the Molecular Revolution - Vivas-Reyes, Ricardo; Navarro, Daniela; Cortes, Luis E. (Journal of chemical education, 2024)
This contribution delves into the intersection of philosophy and chemistry education by exploring the concepts of emergent properties and Félix Guattari’s “molecular revolution”. It highlights the pivotal role these philosophical ideas play in enriching the pedagogy of chemistry, offering new perspectives on the intricate relationship between molecular processes and macroscopic phenomena. The study proposes the integration of these concepts into chemistry education to foster a comprehensive understanding of chemical systems, emphasizing the importance of interdisciplinary approaches. Through practical cases and exercises, the paper demonstrates the application of these ideas in the classroom, particularly in enhancing students’ critical thinking and problem-solving skills. It also addresses the challenges faced by students in grasping the complexity of emergent properties, advocating for a shift from traditional reductionist views to a more holistic and dynamic understanding of chemistry. The findings suggest a paradigm shift in chemistry education, promoting the incorporation of diverse philosophical perspectives to facilitate a deeper engagement with the subject matter. Ultimately, the paper underscores the need for continuous adaptation of teaching methodologies to accommodate the evolving nature of chemical education and its broader implications.